2006
DOI: 10.3748/wjg.v12.i30.4773
|View full text |Cite
|
Sign up to set email alerts
|

Current and future applications ofin vitromagnetic resonance spectroscopy in hepatobiliary disease

Abstract: Nuclear magnetic resonance spectroscopy allows the study of cellular biochemistry and metabolism, both in the whole body in vivo and at higher magnetic field strengths in vitro . Since the technique is non-invasive and non-selective, magnetic resonance spectroscopy methodologies have been widely applied in biochemistry and medicine. In vitro magnetic resonance spectroscopy studies of cells, body fluids and tissues have been used in medical biochemistry to investigate pathophysiological processes and more recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 84 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…Nagana Gowda et al have also analyzed bile samples from various malignant and non-malignant liver disease patients and observed significant changes in the levels of glycine-and taurine-conjugated bile acids [4,5]. Conjugation pattern of bile acids in bile is altered during cholestasis, and determining this pattern in humans could be valuable in the diagnosis of various cholestatic diseases [4,5,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagana Gowda et al have also analyzed bile samples from various malignant and non-malignant liver disease patients and observed significant changes in the levels of glycine-and taurine-conjugated bile acids [4,5]. Conjugation pattern of bile acids in bile is altered during cholestasis, and determining this pattern in humans could be valuable in the diagnosis of various cholestatic diseases [4,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…The composition of bile is altered in various chronic cholestatic diseases [2][3][4][5][6][7][8]. The ratio of taurine to glycine conjugated bile acids is especially altered and it has been reported that the taurine conjugates are elevated in cholestatic conditions [9]. Analysis of bile for the quantification of biliary lipids and for the determination of the conjugation pattern of bile acids (with glycine and/or taurine) would be of value in understanding the pathophysiology of cholestatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This has been termed a ‘metabonomic’ or ‘metabolomic’ approach 8 . In vitro MRS studies on bile have provided information on composition, structure and function, as well as on the metabolism and biliary excretion of xenobiotics 9–11 . A major advantage of the technique is that the sample can be studied intact, which allows for subsequent study as required.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has some minor limitations associated mainly to the spinning of the sample (spinning side-bands, spinning degradation effects and spinning temperature gradients among others), HR-MAS NMR is a non-destructive technique, which requires minimal sample preparation, and allows the observation of most of the tissue metabolites and dynamic interactions in an extremely reduced sample quantity. This technology can supplement histopathological examination and improve liver disease diagnostics (21,28,36,37). The similarities between 'ex vivo' and 'in vivo' spectra found in studies of different tumours allow better interpretation of in vivo MR spectra and increase the clinical potential of the method (38).…”
Section: Introductionmentioning
confidence: 99%